PERANAN ADMINISTRASI DAN MANAJEMEN DALAM MENSUKSESKAN PROGRAM SPORT FOR ALL - Ahadin Ahadin. (Jurnal Pesona Dasar, 2020)
Organizational development or ideas that are owned by mankind generally have similarities, such as the desire to carry out activities, building a certain sports institution requires a coordinated joint effort, therefore humans need an administration, namely an organization that functions to run a joint venture has been made with a specific purpose. Administration is an organization that is run with the ability, efficiently, stays on purpose, with individuals working with a clear, happy, cooperative, and productive guide, in achieving a predetermined goal. To achieve predetermined goals, a management is needed. or a leader who masters human relations, has the ability to predict the future, can make a plan, has the capacity to coordinate the abilities of individuals in the organization. In an effort to make the Sport for All program a success, a leader should have: conceptual skills, self-integrity, skills to relate to people, ability to make decisions, have good physical health and fitness, have a desire to accept responsibility, have skills to use command or command. command, has intellectual capacity. Sport for All is an international community movement in the success of sports with the concept that sport is: a necessity, a means of recreation, for the reinvention of culture, traditional sports, as a realization of the International Charter on physical education and sports UNESCO, namely the United Nations agency in the field of science and culture.